Effect of early and systematic integration of palliative care in patients with advanced cancer: a randomised controlled trial. Issue 3 (March 2018) - Vanbutsele, Gaëlle; Pardon, Koen; Van Belle, Simon; Surmont, Veerle; De Laat, Martine; Colman, Roos; Eecloo, Kim; Cocquyt, Veronique; Geboes, Karen; Deliens, Luc
Summary: Background: The benefit of early integration of palliative care into oncological care is suggested to be due to increased psychosocial support. In Belgium, psychosocial care is part of standard oncological care. The aim of this randomised controlled trial is to examine whether early and systematic integration of palliative care alongside standard psychosocial oncological care provides added benefit compared with usual care. Methods: In this randomised controlled trial, eligible patients were 18 years or older, and had advanced cancer due to a solid tumour, an European Cooperative Oncology Group performance status of 0–2, an estimated life expectancy of 12 months, and were within the first 12 weeks of a new primary tumour or had a diagnosis of progression. Patients were randomly assigned (1:1), by block design using a computer-generated sequence, either to early and systematic integration of palliative care into oncological care, or standard oncological care alone in a setting where all patients are offered multidisciplinary oncology care by medical specialists, psychologists, social workers, dieticians, and specialist nurses. The primary endpoint was change in global health status/quality of life scale assessed by the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 items (EORTC QLQ C30) at 12 weeks. The McGill Quality of Life Questionnaire (MQOL), which includes the additional existential wellbeing dimension, was also used. Analysis was by intention to treat. This trial is ongoing, but closed for accrual, and is registered withClinicalTrials.gov, numberNCT01865396 . Findings: From April 29, 2013, to Feb 29, 2016, we screened 468 patients for eligibility, of whom 186 were enrolled and randomly assigned to the early and systematic palliative care group (92 patients) or the standard oncological care group (94). Compliance at 12 weeks was 71% (65 patients) in the intervention group versus 72% (68) in the control group. The overall quality of life score at 12 weeks, by the EORTC QLQ C30, was 54·39 (95% CI 49·23–59·56) in the standard oncological care group versus 61·98 (57·02–66·95) in the early and systematic palliative care group (difference 7·60 [95% CI 0·59–14·60]; p=0·03); and by the MQOL Single Item Scale, 5·94 (95% CI 5·50–6·39) in the standard oncological care group versus 7·05 (6·59–7·50) in the early and systematic palliative care group (difference 1·11 [95% CI 0·49–1·73]; p=0.0006). Interpretation: The findings of this study show that a model of early and systematic integration of palliative care in oncological care increases the quality of life of patients with advanced cancer. Our findings also show that early and systematic integration of palliative care is more beneficial for patients with advanced cancer than palliative care consultations offered on demand, even when psychosocial support has already been offered. Through integration of care, oncologists and specialised palliative care teams should work together to enhance the quality of life of patients with advanced cancer. Funding: Research Foundation Flanders, Flemish Cancer Society (Kom Op Tegen Kanker).